Tukun tiruan Malaysia : habitat tiruan melestarikan perikanan laut - Raja Mohammad Noordin Raja Omar; Che Omar Mat Hussin; Rosdi Mohd. Nor; Sukarno Wagiman (Kuala Lumpur : Jabatan Perikanan Malaysia, 1994)
28